2003
DOI: 10.1093/jnen/62.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Retinoblastoma Protein in Parkinson Disease

Abstract: Cellular mechanisms implicated in Parkinson disease (PD) include oxidative stress, inflammatory response, excess dopamine, DNA damage, and loss of trophic support. These stimuli have been observed to induce changes in cell cycle proteins in several cell types. One of the key regulators of cell cycle progression is the retinoblastoma protein (pRb); therefore, we assessed the staining for pRb and its inactive hyperphosphorylated isoform, ppRb, in autopsy tissue from patients with PD. In PD we found abundant pRb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 40 publications
6
71
0
Order By: Relevance
“…Although BrdU incorporation may also result from DNA repair, the concomitant expression of cell cyclerelated proteins suggests that it was most likely caused by DNA duplication. Our observations together with other studies (10,13) therefore suggest that the cell cycle-related signals observed in PD patients and models of the disease are functionally relevant and lead effectively to DNA synthesis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although BrdU incorporation may also result from DNA repair, the concomitant expression of cell cyclerelated proteins suggests that it was most likely caused by DNA duplication. Our observations together with other studies (10,13) therefore suggest that the cell cycle-related signals observed in PD patients and models of the disease are functionally relevant and lead effectively to DNA synthesis.…”
Section: Discussionsupporting
confidence: 80%
“…There is some evidence that in PD DNs activate the molecular cell-cycle program. Phosphorylation of the retinoblastoma protein (pRb), a molecular trigger of cell-cycle progression, is observed in DNs in the postmortem SNc of PD patients (10). Likewise, cyclin E promotes S-phase entry and is a substrate of the ubiquitin-ligase parkin, mutations of which have been linked to familial PD (11).…”
mentioning
confidence: 99%
“…Because pRb phosphorylation status has been used as a reliable marker of cell cycle reentry of postmitotic neurons in a host of neurodegenerative disease and injury states (Hayashi et al, 2000;Osuga et al, 2000;Ranganathan et al, 2001;Wang et al, 2002;Jordan-Sciutto et al, 2003;Nguyen et al, 2003), we examined by Western blot analysis whether oxidative stress induces pRb phosphorylation. Compared with the pRb and phosphorylated forms of pRb that can be detected in lysates from the proliferating hippocampal HT22 cell line, pRb in untreated control cell lysates was detected as a single hypophosphorylated band, consistent with E17 rat embryoderived mixed immature cortical cells being predominantly postmitotic (Fig.…”
Section: Oxidative Glutamate Toxicity In Embryonic Cortical Neuronal mentioning
confidence: 99%
“…In addition, in a variety of disorders, cell cycle proteins reappear in neurons at risk for degeneration. These disorders include stroke (Love, 2003), amyotrophic lateral sclerosis (Ranganathan et al, 2001;Nguyen et al, 2003), Parkinson's disease (Jordan-Sciutto et al, 2003), and Alzheimer's disease (AD) (Arendt et al, 1996;Vincent et al, 1996;McShea et al, 1997;Nagy et al, 1997;Busser et al, 1998;Yang et al, 2003). In AD, fluorescence in situ hybridization (FISH) further reveals that DNA replication occurs in the at-risk neurons (Yang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%